How Do Korean Secondary School Teachers Perceive Psychological Burnout in Their Teaching Careers? - Taeeun Shim; Mikyung Jun; Song Yi Lee (Behavioral Sciences)
The psychological burnout experienced by teachers is not merely a personal issue; it is a significant social problem that impacts the entire educational environment. This study utilised Q methodology to identify the subjective perceptions of psychological burnout among Korean secondary school teachers and then analysed the characteristics of these perception types. An analysis of 34 statements and a P sample of 30 teachers resulted in four types of perceptions regarding teachers’ psychological burnout: ‘burnout due to damaged self-esteem’ (Type 1), ‘burnout due to organisational neglect’ (Type 2), ‘burnout due to excessive role demands’ (Type 3) and ‘burnout due to disrespectful behaviour’ (Type 4). This study’s meaningfulness is in its classification of teachers’ psychological burnout into types and its exploration of the types’ features. The results can also help in developing specific intervention programmes for each type.